Impact of Dinophysis acuminata Feeding Mesodinium rubrum on Nutrient Dynamics and Bacterial Composition in a Microcosm - Gao, Han (Toxins (Basel), 2018)
The development of Dinophysis populations, producers of diarrhetic shellfish toxins, has been attributed to both abiotic (e.g., water column stratification) and biotic (prey availability) factors. An important process to consider is mixotrophy of the Dinophysis species, which is an intensive feeding of the Mesodinium species for nutrients and a benefit from kleptochloroplasts. During the feeding process, the nutritional status in the environment changes due to the preference of Mesodinium and/or Dinophysis for different nutrients, prey cell debris generated by sloppy feeding, and their degradation by micro-organisms changes. However, there is little knowledge about the role of the bacterial community during the co-occurrence of Mesodinium and Dinophysis and how they directly or indirectly interact with the mixotrophs. In this study, laboratory experiments were performed to characterize the environmental changes including those of the prey present, the bacterial communities, and the ambient dissolved nutrients during the co-occurrence of Mesodinium rubrum and Dinophysis acuminata. The results showed that, during the incubation of the ciliate prey Mesodinium with its predator Dinophysis, available dissolved nitrogen significantly shifted from nitrate to ammonium especially when the population of M. rubrum decayed. Growth phases of Dinophysis and Mesodinium greatly affected the structure and composition of the bacterial community. These changes could be mainly explained by both the changes of the nutrient status and the activity of Dinophysis cells. Dinophysis feeding activity also accelerated the decline of M. rubrum and contamination of cultures with okadaic acid, dinophysistoxin-1, and pectenotoxin-2, but their influence on the prokaryotic communities was limited to the rare taxa (<0.1%) fraction. This suggests that the interaction between D. acuminata and bacteria is species-specific and takes place intracellularly or in the phycosphere. Moreover, a majority of the dominant bacterial taxa in our cultures may also exhibit a metabolic flexibility and, thus, be unaffected taxonomically by changes within the Mesodinium-Dinophysis culture system.